Thyroid-optimized and thyroid-sparing radiotherapy in oral cavity and oropharyngeal carcinoma: A dosimetric study. (December 2021) - Wu, Anna K.; Damico, Nicholas J.; Healy, Erin; Kharouta, Michael Z.; Khandel, Ghazal; Deshane, Alok; Sipos, Jennifer; Eckstein, Jacob; Zoller, Wesley; Ewing, Ashlee; Ling, Stella; Wobb, Jessica; et al.
Highlights: This feasibility study showed thyroid sparing in head and neck cancer patients. Thyroid sparing with acceptable target volume coverage was possible with IMRT. Average mean dose to thyroid was significantly reduced with thyroid optimization. Thyroid optimized plans had relatively unchanged doses to surrounding OARs. Abstract: Background: Radiation-induced hypothyroidism is a common toxicity of head and neck radiation. Our re-planning study aimed to reduce thyroid dose while maintaining target coverage with IMRT. Methods: We retrospectively identified patients with oral-cavity (n = 5) and oropharyngeal cancer (n = 5). Treatment plans were re-optimized with 45 Gy thyroid mean dose constraint, then we cropped the thyroid out of PTVs and further reduced thyroid dose. Target coverage was delivering 100% dose to ≥ 93% of PTV and 95% of dose to > 99% of PTV. Results: Originally, average mean dose to thyroid was 5580 cGy. In model I, this dropped to 4325 cGy (p < 0.0001). In model II, average mean dose was reduced to 3154 cGy (p < 0.0001). For PTV low and PTV int, all had acceptable target coverage. Conclusion: In patients with oral-cavity and oropharyngeal cancers, mean dose could be significantly reduced using a thyroid-optimized or thyroid-sparing IMRT technique with adequate coverage.